Descrição bioquímica e fisiológica da maturação dos frutos de tomateiro - V L Medina, Paulo; M T Medina, Regina (Revista Ceres, 2025)
Tomato plants, cv. Veegan, were grown in a greenhouse. Uniform production of fruits per plant was attained by restricting the fruit load per cluster. The fruits were picked at various intervals after anthesis from 10-110% of development. Fruit respiration and ethylene evolution were determined daily. The respiratory peak and ethylene production tend to occur at different times after harvest.